Growth and weight status of Brazilian children with autism spectrum disorders: A mixed longitudinal study - Chrystiane V.A. Toscano; José P. Ferreira; Joana M. Gaspar; Humberto M. Carvalho (Elsevier, 2019)
Objective: This study examined the growth status and physical development of Brazilian children with autism spectrum disorders from 4 to 15 years of age. Furthermore, it was examined whether variation in growth patterns and weight status was influenced by the use of psychotropic medications. Methods: One-hundred and twenty children aged 3.6-12.1 years at baseline (average = 7.2 years, SD = 2.3 years) diagnosed with autism spectrum disorders were measured on three repeated occasions across a 4-year period. Stature, body mass, and body mass index were considered. Bayesian multilevel modeling was used to describe the individual growth patterns. Results: Growth in stature was comparable to the age-specific 50th percentile for Centers for Disease Control and Prevention reference data until approximately 8 years, but a substantial decrease in growth rate was observed thereafter, reaching the age-specific 5th percentile at 15 years of age. Both body mass and body mass index values were, on average, higher than both the Brazilian and Centers for Disease Control and Prevention age-specific 95th percentile reference until 8 years, but below the 50th specific-age percentile at the age of 15 years. Conclusions: Brazilian boys with autism spectrum disorders between 4 and 15 years appear to have impaired growth in stature after 8-9 years of age, likely impacting pubertal growth. A high prevalence of overweight and obesity was observed in early childhood, although a trend of substantial decrease in body mass and body mass index was apparent when children with autism spectrum disorders entered the years of pubertal development. Resumo: Objetivo: Este estudo examinou o estado de crescimento e o desenvolvimento físico de crianças brasileiras com transtornos do espectro autista entre 4 e 15 anos de idade. Adicionalmente, examinamos se a variação nos padrões de crescimento e na massa corporal foi influenciada pelo uso de medicamentos psicotrópicos. Métodos: 120 crianças com idades entre 3,6 e 12,1 anos no início do estudo (média = 7,2 anos, DP = 2,3 anos) diagnosticadas com transtornos do espectro autista foram avaliadas em três ocasiões repetidas em um período de 4 anos. Foram considerados estatura, massa corporal e índice de massa corporal. O modelo multinível bayesiano foi utilizado para descrever os padrões de crescimento individual. Resultados: O crescimento em estatura foi comparável ao percentil 50 específico para a idade para os dados de referência do Centro de Controle e Prevenção de Doenças dos Estados Unidos até cerca de 8 anos. Porém, foi observada uma redução substancial na taxa de crescimento depois dos 8 anos, atingindo o percentil 5 específico para a idade aos 15 anos de idade. Tanto os valores de massa corporal quanto de índice de massa corporal foram, em média, maiores comparativamente ao percentil 95 específico para a idade até aos 8 anos da referência brasileira e do Centro de Controle e Prevenção de Doenças dos Estados Unidos, porém abaixo do percentil 50 específico para a idade aos 15 anos de idade. Conclusões: Os meninos brasileiros com transtornos do espectro autista entre 4 e 15 anos parecem ter retardo do crescimento na estatura após os 8-9 anos, provavelmente afeta o crescimento púbere. Foi observada uma alta prevalência de sobrepeso e obesidade na primeira infância, apesar de uma tendência de redução substancial na massa corporal e no índice de massa corporal ter sido aparente quando as crianças com transtornos do espectro autista entraram nos anos de desenvolvimento púbere. Keywords: Obesity, Autism, Anthropometry, Mental health, Bayesian multilevel modeling, Psychotropic medication, Palavras-chave: Obesidade, Autismo, Antropometria, Saúde mental, Modelo multinível bayesiano, Medicação psicotrópica